Excel solver as the software to construct MUSA model - Thiruchelvam, Loshini; Ahmad, Sabri (Global Journal of Mathematical Analysis, 2014)
The study discusses steps to construct MUSA Model using Excel Solver software. This software applies the linear programming approach as needed, in the ordinal regression MUSA Model, with ordinal scaled data set It was found that the Excel Solver could construct the MUSA Model well. Even though the data set need to be re-coded again in Excel Solver, the cheaper cost and availability of this software makes it’s as a good option too.
Keywords: Multi-Criteria Satisfaction Analysis (MUSA); Excel Solver; Linear Programming Approach.